Evaluation of acute toxicity and the effect of single injected doses of zerumbone on the kidney and liver functions in Sprague Dawley rats - Ibrahim, Mohammed Yousif; Abdul, Ahmad Bustamam; Tengku Ibrahim, Tengku Azmi; Abdelwahab, Siddig Ibrahim; Elhassan Taha, Manal Mohamed; Syam, M. M. (Academic Journals, 2010)
Zerumbone is a natural monosesquiterpene isolated from the rhizomes of Zingiber zerumbet Smith. This bioactive compound has been previously shown to have chemo-preventive, anti-inflammatory and free radical scavenging activities. This study was designed to determine the median lethal dose (LD 50) of zerumbone and the effect of three different single doses of zerumbone below the LD 50 on blood biochemistry, hepatic and renal histopathologies and lipid peroxidation in rats. In the LD 50 experiment, eight groups of animals (n = 5) were injected with various doses of zerumbone (100 - 3000 mg/kg, i.p). The animals were observed continuously for clinical change and mortality. Next, zerumbone was injected in single doses (100, 200 and 500 mg/kg) and sacrificed 24 h later. Probit analysis of this study showed that the LD 50 of this compound is 1.84 gm/Kg. Results from this study further suggested that single injected doses of zerumbone at 100 - 200 mg/kg had no ill effect towards the liver and renal tissues of female Sprague Dawley rats. To our knowledge, this paper is the first to report the toxicity effects of zerumbone in rodents.